Neuroprotective Effects Of Xanthone-Enriched Fraction Garcinia Mangostana And Alpha-Mangostin In Chronic Cerebral Hypoperfusion Rats - Tiang, Ning (2021)
In this study, the protective effect of xanthone enriched fraction of G. mangostana (XEFGM) and α-MG were evaluated in an animal model of VaD induced by chronic cerebral hypoperfusion also known as- two vessel occlusion (2VO). In the first part of this study, XEFGM (25, 50, and 100 mg/kg) and α-MG (25 and 50 mg/kg) were administrated to 2VO rats and the rats were then subjected to behavioral test for learning and reference memory evaluation. The result suggested that, 50 mg/kg of α-MG treated 2VO significantly improved spatial learning and reference memory in Morris water maze test.